2018
DOI: 10.24167/celt.v18i1.1212
|View full text |Cite
|
Sign up to set email alerts
|

Promoting EFL Student Teachers’ Life-Long Learning through Microteaching Lesson Study

Abstract: The success of lesson study as an approach for teacher professional development in improving students’ learning has inspired the works on microteaching lesson study which is designed for student teachers in microteaching course. Some studies show that microteaching lesson study brought about positive result to student teachers’ pedagogical ability and content knowledge. However, that microteaching lesson study influences student teachers in their teaching internship, that is the course taken after microteachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
1
6
0
2
Order By: Relevance
“…Bentuk praktek mengajar dilaksanakan sederhana, di mana calon guru berada dalam suatu lingkungan kelas yang terbatas dan terkontrol serta hanya mengajarkan satu konsep dengan menggunakan satu atau dua keterampilan dasar mengajar. Konsep micro teaching dilandasi oleh pokok-pokok pikiran sebagai berikut (Suryani et al, 2018): 1. Pembelajaran bersifat nyata (dilaksanakan dalam bentuk yang sebenarnya), tetapi berkonsep mini, yang memiliki karakter dasar: 2. latihan terpusat pada keterampilan dasar mengajar, 3. mempergunakan informasi dan pengetahuan tentang tingkat belajar siswa sebagai umpan balik terhadap kemampuan calon guru, 4. pembelajaran dilaksanakan bagi para siswa dengan latar belakang yang berbeda-beda dan berdasarkan pada kemampuan intelektual kelompok usia tertentu, 5.…”
Section: Diterimaunclassified
See 1 more Smart Citation
“…Bentuk praktek mengajar dilaksanakan sederhana, di mana calon guru berada dalam suatu lingkungan kelas yang terbatas dan terkontrol serta hanya mengajarkan satu konsep dengan menggunakan satu atau dua keterampilan dasar mengajar. Konsep micro teaching dilandasi oleh pokok-pokok pikiran sebagai berikut (Suryani et al, 2018): 1. Pembelajaran bersifat nyata (dilaksanakan dalam bentuk yang sebenarnya), tetapi berkonsep mini, yang memiliki karakter dasar: 2. latihan terpusat pada keterampilan dasar mengajar, 3. mempergunakan informasi dan pengetahuan tentang tingkat belajar siswa sebagai umpan balik terhadap kemampuan calon guru, 4. pembelajaran dilaksanakan bagi para siswa dengan latar belakang yang berbeda-beda dan berdasarkan pada kemampuan intelektual kelompok usia tertentu, 5.…”
Section: Diterimaunclassified
“…Bagi dosen pengampu mata kuliah dengan adanya hasil penilaian tersebut dapat menjadi dasar untuk memperbaiki pelaksanaan perkuliahan, terutama persiapan dan strategi mengajar, dalam melatih mahasiswa. Sedangkan bagi Prodi PGSD FKIP Universitas Mataram, hasil belajar dapat digunakan sebagai acuan apakah pelaksanaan perkuliahan sudah dilaksanakan sesuai harapan atau belum (Suryani et al, 2018).…”
Section: Hasil Belajar Micro Teachingunclassified
“…Although LS has been implemented in both in-service and pre-service EFL teacher education contexts abroad and in Turkey, MLS requiring a reduced lesson length and a class size including either students or peers (Fernandez, 2005;Fernandez, 2010) has mostly been the subject of preservice teacher education in such fields as mathematics and elementary education in studies in Turkey (Akbaba Dağ & Doğan Temur, 2018;Aldemir, 2017). Furthermore, the number of research studies using MLS in EFL contexts is limited to a few international studies concluding that MLS can promote pre-service EFL teachers' life-long learning to teach the English language, teaching practices and reflective skills (Nguyen, 2020;Suryani, 2016;Suryani et al, 2017;Suryani et al, 2018). To the best of the researcher's knowledge, no studies involving student teachers in an MLS procedure have been conducted in the EFL context of Turkey.…”
Section: Lesson Study In English Language Teacher Educationmentioning
confidence: 99%
“…Therefore, based on the LS approach, MLS emerged as an approach for pre-service teachers by combining elements of LS and microteaching (Fernandez, 2005). Unlike LS in which the lessons are taught to usual classes for usual class length, the lessons in MLS are presented to a smaller group of students or a group of peers for shorter length of class hour (Fernandez, 2010;Suryani et al, 2018). In studies outside the field of pre-service EFL teacher education, it was found that MLS paved the way for reform-oriented teaching, active learning through discussions, planning, support from a knowledgeable advisor, collaboration with peers, and opportunity to try, analyze and revise (Fernandez, 2005;Fernandez, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, studies that focus on PCK are still lacking irrespective of the fact that it is extremely important for pre-service teachers because it aids them to effectively carry out the instructional processes. On the contrary, PCK is commonly developed during microteaching (MLS) (Birel & Ҫakiroğlu, 2018;Cavin, 2007;Suryani, Rukmini, Bharati, & Hartono, 2017;Zhou, Xu, & Martinovic, 2017).…”
Section: Introductionmentioning
confidence: 99%